Evaluation of the Influence of a Chosen Element of Insurance Companies' Employees Behaviour of on Specific Aspects of Customer Relations Management - Grzebieniak, Andrzej (Olsztyn Economic Journal, 2013)
Evaluation of the influence of a selected component of the insurance companies' employees' behaviour on the specific aspects of customer relations management was the objective of the paper. In the paper the hypothesis was assumed that appropriate development of customer relations depends to a large extent on the behaviours of employees defined mainly in the company management strategy in which strictly defined procedures in that area are indicated and appropriate technical, information, IT and organisation and management means are assured. The evaluation was made based on own surveys in which the questionnaire method was used. The mail or Internet questionnaire was the research tool. The questionnaires were distributed to 63 insurance companies possessing their registered offices in Poland during the years 2009-2011. In total, 57 completely and correctly completed questionnaires were returned.